Intermittent Fasting as a complementary Strategy to Manage Type II Diabetes and Metabolic Health: A Review - Mustafa, Faheem; Murtaza, Asifa; Batool, Razzia; Faisal, Samra; Umar, Rabiatul Adawiyah Binti; Khaliq, Muniba; Taib, Wan Rohani Wan; Taha, Che Suhaili Binti Che (Scripta Medica, 2026)
As an alternative or supplement to traditional pharmaceutical treatments, intermittent fasting (IF) has become a viable dietary approach for the management of type 2 diabetes mellitus (T2DM). Improved insulin sensitivity and blood glucose management are the outcomes of various IF patterns, such as time-restricted eating, alternate-day fasting and the 5:2 diet, which encourage a metabolic shift from glucose to fat utilisation. Even in patients on insulin therapy, research indicates that IF may help lower fasting blood sugar, glycated haemoglobin (HbA1c) and insulin resistance with no risk of hypoglycaemia when appropriately monitored. Physiological benefits of IF include enhanced circadian rhythm alignment, increased autophagy, reduced oxidative stress and improved lipid metabolism. Comparisons with other dietary approaches, such as the Mediterranean, Palaeolithic, ketogenic and fasting-mimicking diets, indicate that IF offers flexibility and long-term sustainability for many individuals. However, consistent adherence and personalised strategies are essential for optimal results. Overall, IF presents a valuable complementary approach for managing T2DM and promoting better metabolic health.